Action and Possibility: Reconciling Dual Perspectives of Knowledge in Organizations - Hargadon, Andrew; Fanelli, Angelo (Organization Science, 2002)
At times knowledge can be seen as the source of organizational innovation and change—at other times, however, it can be the very constraint on that change. This conflicted role offers insights into why the phenomenon of organizational knowledge has been interpreted by researchers in multiple and possibly conflicting ways. Some theories depict knowledge as an empirical phenomenon, residing in action and becoming “organizational” in the acquisition, diffusion, and replication of those actions throughout the organization. Others consider it a latent phenomenon, residing in the possibility for constructing novel organizational actions. This paper argues that while each of these qualities—empirical and latent—are intrinsic to knowledge in organizations, our understanding of organizational phenomena is essentially incomplete until the relationship between them is considered. Building on structuration theory, we propose a complementary perspective that views organizational knowledge as the product of an ongoing and recursive interaction between empirical and latent knowledge, between knowledge as action and knowledge as possibility. We ground this complementary model of knowledge in evidence from the field study of two firms whose innovation practices provide unique insights into how knowledge simultaneously enables and constrains behavior in organizations. We then discuss how a complementary perspective avoids the reification of knowledge by depicting it instead as an ongoing and social process and offers an alternative distinction between individual and collective knowledge.